2018
DOI: 10.1007/s00038-018-1092-8
|View full text |Cite
|
Sign up to set email alerts
|

eHealth as a facilitator of equitable access to primary healthcare: the case of caring for non-communicable diseases in rural and refugee settings in Lebanon

Abstract: Low-cost eHealth netbook application was deemed effective in identifying new cases of NCDs and establishing appropriate referrals in underserved communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…These isolates could have been acquired while people were visiting other countries where CL is endemic and then imported foreign strains of L. tropica after they return as previously suggested [15]. Isolates LT1, LT2 and Kubba collected from Lebanon and Syria, respectively, clustered together under population IV consistent with either a transfer event associated with human displacement of refugees [61][62][63][64][65] crossing the Syrian-Lebanon border or movements of the sandfly vector.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 68%
“…These isolates could have been acquired while people were visiting other countries where CL is endemic and then imported foreign strains of L. tropica after they return as previously suggested [15]. Isolates LT1, LT2 and Kubba collected from Lebanon and Syria, respectively, clustered together under population IV consistent with either a transfer event associated with human displacement of refugees [61][62][63][64][65] crossing the Syrian-Lebanon border or movements of the sandfly vector.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 68%
“…Telemedicine could be a promising strategy [39]. It was found that e-health might be a facilitator in gaining access to health care as well as to overcoming transport barriers [40,41]. It was also recommended that strengthening continuity of care for refugees could be achieved through patient-held personal health records [42].…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of a larger study that employed a community mapping approach where adults residing in several rural areas of Lebanon were screened for chronic disease(s) and consequently referred to primary healthcare centers [11,12].…”
Section: Methodsmentioning
confidence: 99%